Analisis Pengaruh Peningkatan Volume Water Basin Tank Cooling Tower terhadap Efisiensi Kinerja Main Gas Blower di PT. XYZ - Taruna, Robert Candra; Lisa Puspita Ariyanto; Putri Sundari (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The efficiency of cooling systems is highly critical in energy industries and industrial processes, particularly in the production of liquid sulfuric acid (H₂SO₄) which relies heavily on operational efficiency. A key factor determining overall plant efficiency is temperature control in critical components. Failure to dissipate heat effectively can result in performance degradation, increased energy consumption, and equipment damage. Increasing the volume of the cooling tower basin water beyond the minimum required limit is intended to stabilize cold water temperatures or enhance the performance efficiency of both the Cooling Tower (CT) and the Main Gas Blower (MGB). This study quantitatively analyzes the impact of comparing the manufacturer's standard Water Basin Tank (WBT) volume against a modified volume on the operational efficiency parameters of the CT and MGB to validate the optimal operational threshold. The results indicate that the standard manufacturer's water basin yields an average range of 5.3°C, an approach of 10.78°C, an effectiveness of 50.79%, a cooling capacity of 0.9 m³°C/h, and an evaporation loss of 1.6 m³/h. Meanwhile, the modified water basin shows an average range of 6.5°C, an approach of 8.4°C, an effectiveness of 76.95%, a cooling capacity of 1.1 m³°C/h, and an evaporation loss of 1.9 m³/h. As a result of the cooling tower performance, the use of the manufacturer's WBT results in a cooling temperature of 37.5°C, an output power of 2,676.3 kW, an efficiency of 63.6%, and a power loss of 1,530.5 kW. Conversely, the modified WBT demonstrates a cooling temperature of 35.4°C, an output power of 3,725.2 kW, an efficiency of 88.6%, and a power loss of 481.6 kW. The comparison reveals that a lower cooling tower temperature leads to a higher output power, greater efficiency, and lower power loss in the MGB. Based on these findings, the LBC 250 Cooling Tower with a modified water basin demonstrates superior performance for use as a cooling system for the Main Gas Blower at the Acid Plant of PT. XYZ